2005
DOI: 10.1074/jbc.m501359200
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide 1-Phosphate, a Mediator of Phagocytosis

Abstract: The agonist-stimulated metabolism of membrane lipids produces potent second messengers that regulate phagocytosis. We studied whether human ceramide kinase (hCERK) activity and ceramide 1-phosphate formation could lead to enhanced phagocytosis through a mechanism involving modulation of the membrane-structural order parameter. hCERK was stably transfected into COS-1 cells that were stably transfected with the Fc␥RIIA receptor. hCERK-transfected cells displayed a significant increase in phagocytic index in asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
74
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 34 publications
0
74
0
Order By: Relevance
“…Shayman and co-workers reported that C1P is formed during phagocytosis and that it promotes the fusion of complex liposomes [14,15]. We recently demonstrated that the calcium-dependent activation of CERK is involved in the degranulation 17 pathway, possibly through the fusion of the plasma membrane with the secretory granules in the mast cells [18].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Shayman and co-workers reported that C1P is formed during phagocytosis and that it promotes the fusion of complex liposomes [14,15]. We recently demonstrated that the calcium-dependent activation of CERK is involved in the degranulation 17 pathway, possibly through the fusion of the plasma membrane with the secretory granules in the mast cells [18].…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, we concluded that the plasma membrane targeting of CERK is induced by the interaction of the PH domain and PI(4,5)P 2 , and, consequently, the translocation of CERK enhances the formation of C1P in the vicinity of the plasma membrane. The translocation might facilitate CERK to interact with their substrates.Shayman and co-workers reported that C1P is formed during phagocytosis and that it promotes the fusion of complex liposomes [14,15]. We recently demonstrated that the calcium-dependent activation of CERK is involved in the degranulation 17 pathway, possibly through the fusion of the plasma membrane with the secretory granules in the mast cells [18].…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Ceramide may be phosphorylated to ceramide-1-PO 4 in the plasma membrane (52). Ceramide kinase activity has been isolated from several cell lines and tissues and is Ca 2+ stimulatable, in contrast to diacylglycerol kinase, which is Mg 2+ dependent.…”
Section: Ceramide-1-phosphate and Sphingosylphosphocholine Synthesismentioning
confidence: 99%
“…In addition, C1P regulates apoptosis (GomezMunoz, 1998;Gomez-Munoz, 2004), is implicated in the inflammatory response (Chalfant and Spiegel, 2005;Lamour and Chalfant, 2005), and is important in the regulation of phagocytosis (Hinkovska-Galcheva et al, 2005;Hinkovska-Galcheva et al, 1998).…”
Section: Introductionmentioning
confidence: 99%